Preventing marine wildlife crime: An evaluation of legal protection and enforcement perspectives - Nurse, Angus (Frontiers in Conservation Science, 2023)
Introduction Despite growing environmental awareness and the efforts of a variety of Non-Governmental Organisations (NGOs) to influence the wildlife protection policy agenda, wildlife laws remain outside the remit of mainstream criminal justice. Adopting a green criminological perspective, this article considers wildlife crime in respect of threats to UK marine wildlife. It examines the UK’s legal and enforcement framework and the scope and nature of both marine wildlife crime and harms to marine wildlife. Its core question is to consider the extent to which the UK’s wildlife law approach provides for effective wildlife protection and is adequate to deal with the threats facing marine wildlife. Methods The research is a mixed methods study that considers the relevant law, case law and reporting of wildlife crimes as well as the enforcement approach to marine wildlife crime. The article’s methodological approach is socio-legal in nature commencing with a review of the relevant literature on threats to marine wildlife and incorporating analysis of the current law and case law available via the legal databases BAILII and Westlaw. The study also conducted an analysis of licences for disturbance of marine wildlife via an examination of the open access case management database managed by the Marine Management Organisation (MMO) the main enforcement body for marine wildlife incidents in the UK. Results The research identifies that while in principle the UK has robust legal protection for marine wildlife, in practice, policy allows exploitation and disturbance of marine wildlife that causes harm to individual animals and is detrimental to efforts to conserve marine wildlife and marine ecosystems. Discussion This research concludes that in the UK, potentially strong legislation existing on paper is arguably not backed by an effective enforcement regime. The remote nature of marine wildlife incidents, competition between marine wildlife and leisure and commercial activities and the very wording of legislation all create enforcement challenges. This article argues for marine wildlife crime to be integrated into mainstream crime policy linked to other forms of offending and criminal justice policy, rather than being largely seen as a purely environmental issue and a ‘fringe’ area of policing.